Latissimus Denervation: A Review of Evidence - Lopez, Christopher D.; Kraenzlin, Franca; Frost, Christopher; Darrach, Halley; Aravind, Pathik; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2019)
Background Breast reconstruction is becoming an increasingly important and accessible component of breast cancer care. Among the many reconstructive options available, the latissimus dorsi flap has experienced a renewal in popularity because of its favorable properties and outcomes when used for breast reconstruction. However, a limitation unique to latissimus-based reconstruction is inappropriate breast animation postoperatively, due to persistent thoracodorsal innervation of the latissimus dorsi muscle after transfer to the mastectomy site.Methods A comprehensive literature search of PubMed and MEDLINE was conducted for studies investigating the role of thoracodorsal denervation in latissimus-based breast reconstruction. Data on surgical techniques, type of intervention, objective outcome measurements, and patient satisfaction-based outcomes were reported. Additional data included patient sample size, follow-up length, and treatment of thoracodorsal nerve (e.g., resection versus transection and length of transection) when applicable.Results Sixty-six search results were reviewed for inclusion and nine qualified after exclusion criteria for a total of 361 patients undergoing either unilateral or bilateral latissimus flap reconstruction. Successful thoracodorsal denervation rates were included in most studies and outcomes measurements were heterogeneous. Eight out of nine studies included patient-reported symptoms of breast animation postoperatively. Based on these findings, a systematic approach is presented.Conclusion We present this review to elucidate successful practices, identify current gaps in knowledge, and offer a systematic approach to this clinical challenge.
Keywords: thoracodorsal denervation; latissimus dorsi; breast reconstruction